2010
DOI: 10.1111/j.1365-3059.2009.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of four pathotypes of Diplocarpon rosae with species and hybrids of Rosa

Abstract: The interactions of four pathotypes of Diplocarpon rosae with 34 species and hybrids of Rosa were compared in an ongoing search for criteria of potential relevance to rose breeding. There were greater similarities in the resistance-susceptibility interactions of these roses to the pathotypes DA1, CW1 and ZM1, than to a fourth pathotype, DA2. Among the species roses, only those of the section Cinnamomeae were susceptible to DA2 and this susceptibility was transmitted in several cases to hybrid progeny. CW1 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the existence of a twelfth race is postulated based on previous results, though this could not be confirmed. Yokoya et al (2000) and Allum et al (2010) showed that isolate DA2 had the most striking host range. The only species roses it infected were those of the section Cinnamomeae, but some Cinnamomeae hybrids, including R. rugosa hybrids, were also susceptible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the existence of a twelfth race is postulated based on previous results, though this could not be confirmed. Yokoya et al (2000) and Allum et al (2010) showed that isolate DA2 had the most striking host range. The only species roses it infected were those of the section Cinnamomeae, but some Cinnamomeae hybrids, including R. rugosa hybrids, were also susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Four races from the UK were also discovered (Yokoya et al. , 2000; Allum et al. , 2010), and four races were differentiated in Belgium (Leus, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly heterozygous nature of Rosa species is a complicating factor when it comes to genetic mapping. The pseudo-test cross mapping approach (Grattapaglia and Sederoff 1994;Kirst et al 2004;Adam-Blondon et al 2016), developed for highly heterozygous species, allows development of parental maps that are then combined into an integrated map. However, (Gartner et al 2013) showed that, although integrating homologous chromosomes that have been rearranged can produce mathematically and statistically correct maps, they do not necessarily reflect the biological reality of chromosomal rearrangements and meiotic recombination that had happened during the outbred cross.…”
Section: New Qtls Detected On Parental Genetic Mapsmentioning
confidence: 99%
“…Of the more than 140 species in the genus Rosa belonging to the Rosaceae family, (Wissemann 2003;Gudin 2000) only 11 of them are likely to have contributed to the origin of modern cultivars (Gudin 2000). Ploidy levels in roses differ from diploid (2n = 2x = 14) to octoploid (2n = 8x = 56) but modern roses are often tetraploids (2n = 4x = 28) (Roberts et al 2009;Allum et al 2010;Debener and Linde 2009). Rose chromosomes are small; the 2C DNA amount in diploid roses (2n = 2x = 14) ranges from 0.83 to 1.30 pg (Roberts et al 2009).…”
Section: Introductionmentioning
confidence: 99%